A new perspective on Belite-ye'elimite-ferrite cement manufactured from electrolytic manganese residue: Production, properties, and environmental analysis. (January 2023) - Wang, Fan; Long, Guangcheng; Bai, Min; Wang, Jilin; Shi, Yingying; Zhou, Xiang; Zhou, John L.
Abstract: In this research, the electrolytic manganese residue (EMR) based belite-ye'elimite-ferrite (E-BYF) clinker composed of 51.6 % belite, 25.6 % iron phase, 15.8 % ye'elimite and 6.5 % over-burned anhydrite phase was manufactured successfully at 1200 °C _ 30 min by utilizing EMR (45.5 %) and additional CaO and Al2 O3 . The existence of iron-rich and heavy metal phases was a potential driving force for achieving near complete calcination at 1200 °C _30 min. The iron ions (8.4 %) and the over-burned anhydrite phase partially replaced the Al 3+ ions by entering the ye'elimite lattice and provided enough SO3 (5.9 %) to help stabilize ye'elimite and β-C2 S formation, respectively. Layered double hydroxides such as AFm phase and strätlingite formed dense microstructure and improved pastes strength as a new rigid skeleton. The formation of rigid solid skeleton-flexible gel embedded co-support system provided a reliable solution for eliminating inherent strength plateau (3-day of 45.9 MPa and 60-day of 107.0 MPa). In this system, the solid-phase hydrates as the main skeleton offered sufficient rigid-supporting, while the gels hydrates as the auxiliary fluid that filled into the pores of the formed skeleton gave the adequately flexible-supporting. In addition, the pastes showed an excellent stabilization ability of heavy metals. The E-BYF system has great potential in reducing CO2 emissions (0.58 kg/kg and 1.36 kg·/MPa·m 3 ) and cost. This work provides a new perspective for a high-quality solution to the strength plateau while achieving a high value-added utilization of EMR.